Turning ideas into action: planning for non-timber forest product development and conservation - Jong, W. de; Utama, R. (1998)
Effective planning for non-timber forest product (NTFP) development and conservation will ensure the most effective use of scarce resources and maximise the likelihood that the objective will be obtained. NTFP development and conservation is usually a long-term activity and involves the collaboration of a number of different, quite independent parties. This has implications for the kind of planning that needs to be undertaken. Issues confronting the manager planning a NTFP initiative are discussed, highlighting three essential elements: the involvement of stakeholders, the need for good information and the need for biological monitoring. Consideration is given to the problems and opportunities in applying these planning principles to forest-based income activities in a GTZ supported Social Forestry Development Project in Indonesia. Ways are suggested to undertake projects in a step-wise fashion in order to match decisions with information as it becomes available. The point is made that in some cases NTFPs may not be the most appropriate products for development. However, the interests of funders often inappropriately constrain the possibilities for working with agricultural products with greater potential.